PENGARUH KEGIATAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) TERHADAP HASIL BELAJAR PADA MATA PELAJARAN EKONOMI KELAS XI DI SMA NEGERI 1 BONEPANTAI - Piyohu, Belviana; Mahmud, Melizubaida; Maruwae, Abdulrahim; Bahsoan, Agil; Halid, Risca Marsanti (State University of Gorontalo, 2025)
The purpose of this study was to determine whether there was an influence of OSIS on student learning outcomes. This study used a descriptive quantitative approach with a sample size of 35 people. The instrument used was a questionnaire. The data analysis technique used was simple linear regression analysis. Based on the results of the data analysis, it is known that there is a significant influence of 51.2% of the variability regarding the variable of Student Learning Outcomes in the Economics Subject of class XI at SMA Negeri 1 Bonepantai which can be explained by the OSIS Activity variable, while the remaining 48.8% is influenced by other variables not examined in this study.